Santa Clara Valley from Hassler Parkway - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of a valley with fruit trees and fields. A barn and a farm house are visible on the far left. More houses, farm buildings and farm equipment are visible in the background. This photo was probably taken from the viewpoint of Hassler Parkway in San Jose.